Conquering knowledge from images: improving image mining with region-based analysis and associated information - Cazzolato, Mirela Teixeira (2019)
The popularization of social media, combined with the widespread use of smartphones and the use of advanced equipment in hospitals and medical centers has generated single and sequences of complex data, including images of high quality and in large quantity. Providing appropriate tools to extract meaningful knowledge from such data is a big challenge, and taking advantage of existing approaches to find patterns from images can be meaningful. While many potential techniques have been proposed to analyze images, most of the processing performed by image mining techniques consider the entire image. Thus, regions that are not of interest are considered in the analysis step, without proper distinction and consequently damaging most tasks. This doctorate PhD research has the following thesis: The analysis of image regions, combined to additional information, leads to more accurate mining results regarding the entire image, and also helps the processing of sequences of images, speeding-up costly pipelines and making it possible to infer knowledge from objects movement. We evaluate this thesis in three application scenarios. In the first scenario, we analyzed regions of images from emergency situations, gathered from social media and which depict smoke regions. We were able to segment smoke regions and improve the classification of smoke images by up to 23%, compared to global approaches. In the second scenario, we worked with images from the medical context, containing Interstitial Lung Diseases (ILD). We classified the images considering the uncertainty of each lung region to contain different abnormalities, representing the obtained results with a heat map visualization. Our approach was able to outperform its competitors in the classification of lung regions by up to four of five classes of abnormalities. In the third scenario, we dealt with sequences of microscopic images depicting embryos being developed over time. Using region-based information of images, we were able to track and predict cells over time and build their motion vector. Our approaches showed an improvement of up to 57% in quality, and a speed-up of the tracking pipeline by up to 81:9%. Therefore, this PhD research contributed to the state-of-the-art by introducing methods of region-based image analysis for the three aforementioned application scenarios.